Lorenzo de' Medici at home: the inventory of the Palazzo Medici in 1492 - Stapleford, Richard (Pennsylvania State University Press, 2013)
"An inventory of the private possessions of Lorenzo il Magnifico de' Medici, head of the ruling Medici family during the apogee of the Florentine Renaissance"--Provided by publisher